PENGUJIAN RUTIN TRAFO ARUS 24 KV DI LABORATORIUM HUBUNG SINGKAT PT. PLN (PERSERO) PUSLITBANG KETENAGALISTRIKAN - Juara Mangapul Tambunan (Sekolah Tinggi Teknik - PLN, 2018)
The current transformer is one of the instrumen transformers that converts large currents into small current for measurement and protection. Router Current transformer testing is a test performed by the manufacturer of all transformed flow produced, to separate defects of deviates from standard requirements. The result of current transformer test that has been done / observed is as follows: testing of the frequency of the voltage resistance does not occur flash, partial removal test of 4.3 pC and 1.6 pC, testing of more inter-winding voltage of 22.03 V and 52.47 , Insulation resistance testing of 244 GΩ, 352 GΩ and 652 GΩ, testing of winding resistance at 29 ° C at 0.045 Ohm and at 75 ° C at 0.053 ohm. For testing the accuracy of the measurement transformer at burden 1 VA the error ratio is 0.144%, 0.143%, 0.141%, 0.133%, 0.132% and the angle error is 2.20 minutes, 2.13 minutes, 1.97 minutes, 1.34 minutes, 1.23 minutes. For testing the accuracy of the measurement transformer at 10 VA burden the error error is -0.037%, -0.032%, -0.017%, 0.043%, 0.049% and the angle error is 8.10 min, 7.03 min, 4.12 min, 0, 23 minutes, 0.07. For testing the transformer protection accuracy with burden 7.5 error ratio is 0.05% and the angle error is 3.86 minutes.